Active waveband selective switches based on guided‐mode resonance for telecommunications. Issue 3 (1st June 2019) - Ren, Zhibin; Sun, Yahui; Lin, Zihao; Zhang, Kaipeng; Wang, Songli; Li, Mingwen; Lu, Hongsheng
Abstract : Active waveband selective switches for the telecommunication wavebands are fabricated and demonstrated. This type of active waveband selective switch is composed of a guided‐mode resonance filter, a twisted nematic liquid crystal (TN‐LC) layer, and a linear polariser. In voltage‐off status, a fabricated active waveband selective switch with grating period of 893.86 nm exhibits high resonance peak with wavelength around 1311.2 nm. In voltage‐on status, this switch exhibits a high resonance peak with wavelength around 1551.3 nm. The measured reflection peaks of another active waveband selective switch with grating period of 872.84 nm are located at 1309.1 and 1549.4 nm in voltage‐on status and voltage‐off status, respectively. Thus, light waveband can be tuned between O‐band and C‐band by electrically driving the TN‐LC layer of this type of active waveband selective switch in real time.